2008
DOI: 10.1534/genetics.108.090233
|View full text |Cite
|
Sign up to set email alerts
|

Sequence Divergence Impedes Crossover More Than Noncrossover Events During Mitotic Gap Repair in Yeast

Abstract: Homologous recombination between dispersed repeated sequences is important in shaping eukaryotic genome structure, and such ectopic interactions are affected by repeat size and sequence identity. A transformation-based, gap-repair assay was used to examine the effect of 2% sequence divergence on the efficiency of mitotic double-strand break repair templated by chromosomal sequences in yeast. Because the repaired plasmid could either remain autonomous or integrate into the genome, the effect of sequence diverge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
47
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(56 citation statements)
references
References 67 publications
9
47
0
Order By: Relevance
“…In yeast, sgs1⌬ mutants demonstrate a hyperrecombination phenotype when spontaneous homologous recombination is analyzed (22,65,68), but HO-induced recombination (28) and plasmid gap repair (66) are slightly decreased, consistent with our results. In Drosophila, BLM deficiency is associated with a marked decrease in SDSA during gap repair (1,36), which has been proposed to be related to a requirement for helicase activity to support multiple rounds of strand invasion.…”
Section: Discussionsupporting
confidence: 90%
“…In yeast, sgs1⌬ mutants demonstrate a hyperrecombination phenotype when spontaneous homologous recombination is analyzed (22,65,68), but HO-induced recombination (28) and plasmid gap repair (66) are slightly decreased, consistent with our results. In Drosophila, BLM deficiency is associated with a marked decrease in SDSA during gap repair (1,36), which has been proposed to be related to a requirement for helicase activity to support multiple rounds of strand invasion.…”
Section: Discussionsupporting
confidence: 90%
“…Since mitotic crossover can result in LOH throughout the region centromere-distal to the crossover, which can be detrimental, it seems logical that noncrossover repair pathways would predominate. This hypothesis has been supported by several studies that found crossover-associated conversions to be approximately one-quarter to one-third of all conversions (Haber and Hearn 1985;Chua and Jinks-Robertson 1991;Inbar and Kupiec 1999;Nickoloff et al 1999;Yin and Petes 2013), but three studies reported that half or nearly half of all conversions were crossover-associated (Aguilera and Klein 1989;Welz-Voegele and Jinks-Robertson 2008;Yim et al 2014). In this study, among the 79 gene conversions collected from cells grown under replication stress (no galactose), 30% were crossover-associated and 70% were noncrossoverassociated.…”
Section: Association Of Mitotic Gene-conversion Tracts At Fs2 With Crmentioning
confidence: 83%
“…CO suppression is supported biochemically because BLM, together with TOPIIIα and RMI1, migrates Holliday junctions to promote their dissolution (14). Genetic evidence in both yeast and Drosophila support a role for the respective BLM homologs (Sgs1 and MUS309, respectively) in suppressing interhomolog COs at DNA lesions (15)(16)(17). A recent study in human cells is consistent with a similar role of mammalian Blm, although crossing over could not be distinguished from other repair pathways (18).…”
mentioning
confidence: 89%